Interaction Between Demographic Profile of Shoppers, Their Behaviour, and Mall Factors : Evidences from a Shopping Mall in South Africa - Garg, Ajay K.; Atwaru, Yakeen M. (Indian Journal of Marketing, 2017)
This study examined the interplay between demographic profiles of shoppers, mall factors, and behavioural variables, namely frequency of visit, time spent, and money spent. Data were collected from 250 respondents via an anonymous survey method at a shopping mall in South Africa and were analyzed quantitatively using a range of statistical analyses. The key findings of the study are that patrons frequenting suburban malls in the largest numbers were typically young, black, women, married, were in the income bracket of R30000.00 - R39000.00, were working professionals, had a tertiary qualification, lived within two kilometres from the mall, visited the mall several times a week, spent between 1-2 hours at the mall, and spent between R100 – R500 at the mall during each visit. The study further revealed that most of the demographic variables had a statistically significant relationship with frequency of visit and money spent at the mall, while time spent was positively related to gender and marital status. Gender, age, educational level, and dwelling distance were the differentiating demographic factors towards hedonic mall factors (convenience and variety). On the other hand, income was the only demographic variable that showed a differentiating behaviour for the hedonic factor namely, ambience. The study contributed to examine the interplay between mall factors, demographic factors, and behavioural variables.